2016
DOI: 10.1158/1535-7163.mct-15-0717
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-CRR9/CLPTM1L Antibodies with Antitumorigenic Activity Inhibit Cell Surface Accumulation, PI3K Interaction, and Survival Signaling

Abstract: We and others have recently shown Cisplatin Resistance-Related Protein 9 (CRR9)/Cleft Lip and Palate Transmembrane 1-Like (CLPTM1L) to affect survival and proliferation in lung and pancreatic tumor cells. Our research has indicated that CLPTM1L affects multiple survival signaling pathways in tumor cells under oncogenic, genotoxic, and microenvironmental stress. We have confirmed the association of CLPTM1L with pancreatic cancer by demonstrating overexpression of CLPTM1L in pancreatic tumors and poor survival i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…We have investigated CLPTM1L as a potential therapeutic target in pancreatic tumors and its association with mediators of the UPR. Our published data confirms that CLPTM1L is overexpressed in over 90% of pancreatic cancers and that high expression is associated with poor survival . We have demonstrated for the first time that CLPTM1L is expressed on the surface of pancreatic, lung and ovarian tumor cells and its function can be inhibited with antibodies .…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…We have investigated CLPTM1L as a potential therapeutic target in pancreatic tumors and its association with mediators of the UPR. Our published data confirms that CLPTM1L is overexpressed in over 90% of pancreatic cancers and that high expression is associated with poor survival . We have demonstrated for the first time that CLPTM1L is expressed on the surface of pancreatic, lung and ovarian tumor cells and its function can be inhibited with antibodies .…”
Section: Introductionsupporting
confidence: 82%
“…We have demonstrated for the first time that CLPTM1L is expressed on the surface of pancreatic, lung and ovarian tumor cells and its function can be inhibited with antibodies . We have shown that CLPTM1L inhibition with both shRNA and our antibodies robustly inhibited tumorigenesis, anchorage independent growth, Akt phosphorylation, and Bcl‐xL accumulation . Plasma membrane accumulation of CLPTM1L and the interaction of CLPTM1L with PI3K‐alpha in pancreatic tumor cells was enhanced by gemcitabine treatment and ER‐stress induction, but inhibited by anti‐CLPTM1L antibody treatment.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This signal was located in the promoter of CLPTM1L . Increased expression of CLPTM1L was observed associated with cell migration and invasion in lung cancer cells . James MA and colleagues found that rs31489 could regulate the expression of CLPTM1L by detecting the CLPTM1L expression in 32 tumor adjacent normal lung tissues .…”
Section: Discussionmentioning
confidence: 99%
“…The current research on CRR9 has made some breakthroughs. It has shown that CRR9 is abnormally highly expressed in various human malignant tumor tissues and corresponding cell lines, especially in some malignant tumors with high invasiveness and metastasis [17]. CRR9 was first isolated by screening of the cisplatin (CDDP) resistance-related gene.…”
Section: Introductionmentioning
confidence: 99%